Ergonomics risk factors analysis of building construction work in SARBAGITA Region Bali Indonesia - Sudiajeng, Lilik; Yusuf, M.; Santiana, Made Anom; Sutapa, I Ketut; Martin, Bernard (International research journal of engineering, IT and scientific research, 2025)
The main objective of this research is to analyze Ergonomics Risk Factors and MSDs Rate in building construction work in the SARBAGITA area of Bali, Indonesia. SARBAGITA, an acronym for Denpasar, Badung, Gianyar, and Tabanan, is the largest metropolitan area in the Nusa Tenggara Islands and the second largest in the Eastern Indonesia Region after the metropolitan city of Mamminasata in South Sulawesi. Therefore, various infrastructure facilities have been developed, including office buildings, hotels, and other public facilities. The development of infrastructure in the SARBAGITA can be seen through the number of active construction companies. In 2020, the number of active construction companies was 987, decreased slightly during the COVID-19 pandemic in 2021 to 883, and rose again to 997 in 2022. If each company has at least one construction project, then the number of active projects in 2022 was 997. Construction work is very complex, especially in building construction. Involving a large number of workers with varied backgrounds, most of the work is carried out outdoors, using a variety of heavy-duty equipment, and involving hazardous materials. Construction work has a high risk of accidents and work-related diseases from aspects of biology, physics, chemistry, ergonomics, and even psychology.